Advancing Legal and Policy Strategies for Expeditious Geothermal Energy Integration: A Path towards Clean Energy and Energy Security in Indonesia - Fajar, Habib Ferian; Syahputra, Julfahmi; Natijah, Khairun (Faculty of Law Universitas Negeri Semarang, 2023)
This paper delves into the imperative task of advancing legal and policy strategies to expedite the integration of geothermal energy, thereby fostering a pathway toward clean energy and energy security in Indonesia. Recognizing geothermal energy as a renewable and environmentally friendly resource, the research underscores Indonesia's rich potential in this regard. Despite the commitment evidenced by the 2021-2030 Electricity Supply Business Plan (RUPTL) and Presidential Regulation No. 112/2022, the study identifies persistent challenges hindering the swift development of geothermal energy in the country. Employing a normative legal research method, the study scrutinizes the application of legal norms within positive law. Through an extensive literature review, the research highlights key obstacles and suggests crucial legal and policy interventions for overcoming them. The findings emphasize the need for ongoing energy regime stabilization, and the provision of incentives such as governmental support for exploration, fiscal incentives, and low-cost financing schemes for geothermal projects. The paper advocates for a comprehensive approach to address these challenges, recognizing the pivotal role of legal and policy frameworks in propelling sustainable development. By delineating effective strategies, this research contributes to the discourse on transitioning Indonesia towards clean energy alternatives, ensuring energy security, and mitigating the environmental impact of traditional energy sources.